In vitro antibacterial activity of marine-derived fungi isolated from Pulau Redang and Pulau Payar Marine Parks, Malaysia against selected food-borne pathogens - Mat Daud, Noor Ifatul Hanim; Lee, Hai Yen; Saari, Nazamid; Md. Noordin, Wan Norhana; Mahyudin, Nor Ainy (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Marine fungi are potential source of bioactive compounds as indicated by the increasing statistic of research findings. However similar research in Malaysia is still lacking. Hence, this study is undertaken to determine the antibacterial activity of four marine fungal isolates (PR1T4, PP2L4, PR3T13 and PR5T4) from Pulau Redang and Pulau Payar Marine Parks, Malaysia against Salmonella Typhi, Listeria monocytogenes, Staphylococcus aureus, and Escherichia coli. Fungal isolates were first macroscopically and microscopically characterized and later molecularly identified as Penicillium citrinum, Sacroladium strictum, Aspergillus sydowii and Aspergillus sp. respectively. Solid and broth fermentation of fungi were carried out to produce crude extracts and these extracts were screened for antibacterial activity. In general, solid fermentation extracts (SFE) showed significantly higher antibacterial activity (p < 0.05) against all four pathogens compared to broth fermentation extracts (BFE) as the largest inhibitory activity of SFE and BFE was (32.17±0.67 mm) and (27.57±0.81 mm) respectively both on S. aureus by S. strictum. Highest antibacterial activity against L. monocytogenes (27.95±0.81 mm) was exhibited by SFE of A. sydowii while SFE of S. strictum showed highest activity against S. aureus (32.17±0.67 mm) and E. coli (23.53±0.57 mm) and SFE of Aspergillus sp. showed largest inhibition towards S. Typhi (29.30±0.33 mm). These prominent results suggest that all four isolates have potential to be explored as new source of antibacterial agents against food-borne pathogens.